Biomass in the Bioeconomy : Focus on the EU and US - Wertz, Jean-Luc, author 317061; Mengal, Philippe, author 651029; Perez, Serge, author 598907 (Boca Raton : CRC Press, 2023)
"Biomass is the physical basis of the bioeconomy, the renewable segment of the circular economy, and as a CO2-neutral part of the carbon cycle, biomass is an efficient carbon sink. Demand for biomass is increasing worldwide because of its advantages in replacing fossil-based materials and fuels, which presents the challenge of reconciling this increased demand with the sustainable management of ecosystems, including forests and crops. This reference book discusses the role of biomass in the bioeconomy and focuses on the European Union and the United States, the first two regions to develop a bioeconomy strategy with an obvious effect on the bioeconomy developments in the rest of the world. When significant, developments in other areas of the world are addressed. Provides strategies for optimal use of biomass in the bioeconomy. Defines and details sources, production, and chemical composition of biomass. Describes conversion, uses, and sustainability of biomass. Biomass in the Bioeconomy will appeal to an interdisciplinary audience of readers working in the fields of chemical and environmental engineering."--